REPRESENTASI BUDAYA KONSUMEN DI KOMUNITAS MINIMALIS LYFE WITH LESS - Dini Eka Putri (Universitas Pendidikan Nasional, 2021)
The culture of consumerism is almost a pathology for people all over the world. Consumerism culture according to Jean Baudrillard is the fulfillment of the human need for signs. Therefore, it is also necessary to identify a consumerist culture in a minimalist community that has thoughts or principles that are contrary to consumerism. The Lyfe With Less minimalist community or can be shortened to the LWL community is an Indonesian minimalist community. This community is a place for people to learn to be minimalist. Minimalism is closely related to reducing consumption in life, in order to get more happiness. Based on the many programs owned by the LWL community, there is one program that is the hallmark of this community. The programs are cross-linked. The research objective is to answer major and minor questions. The major question is how the interrelationships of consumer culture and processes in the LWL community are interrelated. While the minor question is how the involvement of consumerism culture when the process crosses over. This research method uses a virtual ethnographic qualitative method. The results show that the LWL minimalist community has anti-consumerism thoughts, including cross-linking programs to extend the functionality of goods.